Підвищення кваліфікації адвокатів України: проблеми правового регулювання - Задоя, Іванна Іванівна; Задоя, Иванна Ивановна; Zadoja, Ivanna (Одеса : Юрид. л-ра, 2014)
The article is devoted to complex research of problems of the legal adjusting of the institute of the in-plant training of the advocates in Ukraine. The body corporate and politic of laws, on the basis of that legal adjusting of the species, order of passing and system of evaluation of in-plant training of advocates comes true in Ukraine and the lacks of such legal regulation are certain, is analyzed in the article. Foreign experi- ence of the legal adjusting of the in-plant training of advocates is studied and uggestions are given in the relation to the improvement of the legal adjusting of the home system of in-plant training of advocates of Ukraine.
Задоя І. І. Підвищення кваліфікації адвокатів України: проблеми правового регулювання / І. І. Задоя // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 74. – С. 379-385.
Keywords: адвокати; підвищення кваліфікації; проблеми правового регулювання; адвокаты; повышение квалификации; проблемы правового регулирования; advocates; in-plant training; problem of the legal adjusting